Power minimization in QoS sensitive systems. - Wong, J.L (IEEE Transactions on VLSI systems)
The majority of modern multimedia and mobile systems have two common denominators: quality-of-service (QoS) requirements, such as latency and synchronization, and strict energy constraints. However, until now no synthesis techniques have been proposed for the design and efficient use of such systems. We have two main objectives: conceptual and synthesis. The conceptual objective is to develop a generic practical technique for the automatic development of online adaptive algorithms from efficient off-line algorithms using statistical techniques. The synthesis objective is to introduce the first design technique for QoS low-power synthesis. We introduce a system of provably-optimal techniques that minimize energy consumption of stream-oriented applications under two main QoS metrics: latency and synchronization. Specifically, we study how multiple voltages can be used to simultaneously satisfy hardware constraints and minimize power consumption while preserving the requested level of QoS. The purpose of the off-line algorithm is threefold. First, it is used as input to statistical software which is used to identify important and relevant parameters of the processes. Second, the algorithm provides buffer occupancy rate indicators. Lastly, it provides a way to combine buffer occupancy and QoS metrics to form a fast and efficient online algorithm. The effectiveness of the algorithms is demonstrated on a number of standard multimedia benchmarks.